Analisis Problematika Penerapan Zona Integritas di Balai Diklat Keagamaan Aceh, Bandung, Makassar Dan Papua - Emma Himayaturohmah (Jurnal Kewidyaiswaraan, 2019)
In factual, the integrity zone has been proclaimed to all institutions in Indonesian Ministry of Religious Affairs and training. The intention of implementing this integrity zone is to create a corruption-free and clean-serve territory. In practice, there are several obstacles that impede the process of developing this integrity zone. This research aims to obtain a relatively complete picture of various problematics faced by the Education and Religious Training Halls when implementing the integrity zones development in their environment. At the same time, this study was also intended to obtain an overview of the measures taken in addressing the problems of integrity zones implementation over their work environment. This study was conducted in four Education and Religious Training Halls in the environment of The Agency of Research, Development, Education and Training, Indonesian Ministry of Religious Affairs. They are located in Aceh, Bandung, Makassar, and Papua. The method used in this study is qualitative with a multicase approach. Because it is a qualitative study with a multi-case study design, this research does not intend to generalize as quantitative research. The method revealed various problems that impede the implementation of integrity zone development. The results showed that the application of integrity zones in the environment of Education and Religious Training Halls encountered various obstacles, namely: (1) An incomplete socialization that implicates the lack of insight and understanding of what, why, how and in what way the integrity zone is implemented to the environment of their work units; (2) There is no periodic evaluation that can identify early on various potential issues as well as potencies identification that can be covinated to optimize integrity zone implementation; (3) The lack of supporting infrastructure makes the implementation of integrity zone development can not run optimally; (4) The organizational commitment to integrity zone implementation is relatively low. (5) The peak leadership that has not yet emerged strongly becomes the role model for the basic principles implementation over the institutional integrity. The recommendations offered by this study are: (1) to establish "Integrity Court" suchlike in every education and religious training hall; (2) to develop integrated literacy infrastructure through cyber literacy; (3) to make a litation of the integration as an individual training; (4) to take an institution as a benchmark outside the Ministry of Religious Affairs which has been designated as WBK and WBBM by the Ministry of PAN RB.